Medico-Ethon-Botanical Study of Indigenous and Migrated Medicinal Plants Diversity at Kothi Village in Kangra District of Himachal Pradesh in India: A Cross-Sectional Survey (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda and medicinal plants of folklore are the primary sources of health care in rural areas of India. Medicinal plants are the basis of Ayurveda drugs. Kothi village at an elevation of around 1,100m from the sea level is a hamlet in Kangra District of Himachal Pradesh and it has a good diversity of medicinal plants. The medicinal plants' diversity in this village is not studied to date. This cross-sectional survey study (observational study of descriptive and analytical type) was conducted to discover the diversity of medicinal plants in the Kothi village. The medicinal plant diversity at RGGPGAC&H territory was the sample chosen for this study. The total diversity of medicinal plants in the Kothi village was considered as the population of the study. Questionnaire based interviews and discussions with local villagers and sellers were used as a method for medicinal plants sample collection from the sample area. The sample medicinal plants were then verified by the faculty of PGDD at RGGPGAC&H. After verification, samples were cross-verified with authoritative publications by the government of Himachal Pradesh and India. A total of 151 different indigenous cum migrated medicinal plant diversity belonging to 69 families is found occurring in the Kothi village.